Improvement of Monacolin K and Pigment Production in Monascus by 5-Azacytidine - Chan Zhang; Haijiao Wang; Qing Sun; Arzugul Ablimit; Huijun Dong; Congcong Wang; Duchen Zhai; Bobo Zhang; Wenlin Hu; Chengjian Liu; Chengtao Wang (Journal of Fungi)
Monascus species are known to produce various secondary metabolites with polyketide structures, including Monacolins, pigments, and citrinin. This study investigates the effects of 5-azacytidine on Monascus M1 and RP2. The dry weight, red, yellow, and orange pigment values, and Monacolin K yield of both Monascus strains were measured, and their hyphae observed through electron microscopy. The experimental group showed higher dry weights and pigment values than the control group for both strains. However, Monacolin K production increased substantially only for Monascus M1. Electron micrographs revealed surface wrinkles and large protrusions in both strains after 5-azacytidine treatment. As a potent DNA methylation-promoting agent, 5-azacytidine is very useful for epigenetic and cancer biology studies and for studying secondary metabolism in fungi.